Preliminary study of nanonized lamotrigine containing products for nasal powder formulation - Gieszinger P; Csóka I; Pallagi E; Katona G; Jójárt-Laczkovich O; Szabó-Révész P; Ambrus R (Dove Medical Press, 2017)
Péter Gieszinger, Ildikó Csóka, Edina Pallagi, Gábor Katona, Orsolya Jójárt-Laczkovich, Piroska Szabó-Révész, Rita Ambrus Faculty of Pharmacy, Institute of Pharmaceutical Technology and Regulatory Affairs, University of Szeged, Szeged, Hungary Abstract: The nasal delivery of drugs offers a great alternative route to avoid adverse events and to increase patient compliance due to its advantageous properties. Besides nasal application, topical, systemic and central effects are also available. Nasal powders (NPs) have better adhesion due to the additive polymers that may be, eg, gelling or good wettability agents; thus, their bioavailability is better compared to the liquid formulations. Using nanoparticles, innovative and more efficient products can be achieved, which may lead to the improvement of different therapies. The aim of this study was to produce NP formulations containing lamotrigine (LAM) as interactive physical mixtures and nanosized LAM-based formulations. After risk assessment of the preliminary tests, the micrometric properties (particle size and morphology) and the structural properties (differential scanning calorimetry [DSC], X-ray powder diffraction [XRPD]) were investigated; thereafter, physicochemical properties (solubility, polarity) and in vitro dissolution and diffusion profiles were also examined. These product samples showed an appropriate particle size ranging 10–25 µm, while the particle size of LAM in the products was between 120 and 230 nm and the dissolved amount of drug was >60% after 5 minutes in these cases. Keywords: nanonization, nasal powder, lamotrigine, co-milling, risk assessment